Relación entre el bienestar laboral y la felicidad de los empleados en empresas colombianas (2020)
The well-being and happiness of people not only help in the success of a company, but also lead to loyalty and reduction of circumstances such as stress, disability diseases etc. This undergraduate work seeks to improve the working environment in companies where we can analyze the severity we see in our country, in terms of the treatment of employees, and how we value their skills and knowledge little; therefore, good innovation management and commitment of each manager, leader or boss is recommended, since they will be of great contribution to the fulfillment of the objectives of each company.